2x+7+(3-4)i=4+6i

Simple and best practice solution for 2x+7+(3-4)i=4+6i equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+7+(3-4)i=4+6i equation:


Simplifying
2x + 7 + (3 + -4) * i = 4 + 6i

Combine like terms: 3 + -4 = -1
2x + 7 + (-1) * i = 4 + 6i

Reorder the terms:
7 + -1i + 2x = 4 + 6i

Solving
7 + -1i + 2x = 4 + 6i

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Add '-6i' to each side of the equation.
7 + -1i + -6i + 2x = 4 + 6i + -6i

Combine like terms: -1i + -6i = -7i
7 + -7i + 2x = 4 + 6i + -6i

Combine like terms: 6i + -6i = 0
7 + -7i + 2x = 4 + 0
7 + -7i + 2x = 4

Add '-7' to each side of the equation.
7 + -7i + -7 + 2x = 4 + -7

Reorder the terms:
7 + -7 + -7i + 2x = 4 + -7

Combine like terms: 7 + -7 = 0
0 + -7i + 2x = 4 + -7
-7i + 2x = 4 + -7

Combine like terms: 4 + -7 = -3
-7i + 2x = -3

Add '-2x' to each side of the equation.
-7i + 2x + -2x = -3 + -2x

Combine like terms: 2x + -2x = 0
-7i + 0 = -3 + -2x
-7i = -3 + -2x

Divide each side by '-7'.
i = 0.4285714286 + 0.2857142857x

Simplifying
i = 0.4285714286 + 0.2857142857x

See similar equations:

| 2y-2=12y-13 | | -5-2y=6-6y | | 2x-7/3=11 | | 6x^4/3 | | 15w-60=-12w-35 | | -2/3x+3(5x+40)=-34 | | 2(3x-2)=84 | | 7x-3=-19+3x | | 110+7x= | | 2/(q-1)=3/(q-2) | | 9x+10y=3660 | | -9y-11=12 | | 0=-10-5X^2-27X | | 72+4x= | | 64x^2-2x+1= | | 10k^2=-12 | | 32=32c | | 19-50x= | | c=15385+85 | | p=-10x^2+750x+-9000 | | -4+20=36 | | 10=2x-20 | | 3x-6(-1/3+8)=-3 | | X(X-16)-63=0 | | 2x+6x-80=112 | | 92+78x= | | 0.5x+2.1=0.9x-0.3 | | B-7+2b=31 | | .50x+.25(60)=.25(82) | | 1/2=m-1/8 | | 49+3x= | | 2(5x+20)-4x= |

Equations solver categories